2021
DOI: 10.1287/ited.2019.0227
|View full text |Cite
|
Sign up to set email alerts
|

The Dark Side of Narrow Gamification: Negative Impact of Assessment Gamification on Student Perceptions and Content Knowledge

Abstract: We explored the effects of assessment gamification on students’ content knowledge and perceptions of satisfaction, course experience, learning, and impact of teaching techniques. The course preparation, attendance, quizzes, classroom activities, and team projects of an undergraduate operations and supply chain management course had game elements that accumulate to team advantages in the collaborative midterm and final exam. Interestingly, we found that gamifying assessment activities resulted in significantly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
27
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(29 citation statements)
references
References 39 publications
1
27
1
Order By: Relevance
“…From a theoretical point of view, the most widely used frameworks to explain the relationship between learning and the use of games have been the theory of gamified learning and the self-determination theory (SDT) [30,[41][42][43]. Very succinctly (see a longer description [30,34,[41][42][43][44]) the theory of gamified learning [34] postulated that GBL influences learning through four components-such as instructional content, behaviors and attitudes, game characteristics, and learning outcomes-being the critical issue to the success of any GBL effect that "the instructional content in place is already effective" [34] (p. 9). Self-determination theory (SDT) postulated that "an understanding of human motivation requires a consideration of innate psychological needs for competence, autonomy, and relatedness" [43] (p. 227).…”
Section: Does Game-based Learning Work In Hies? Its Theoretical Foundationmentioning
confidence: 99%
See 1 more Smart Citation
“…From a theoretical point of view, the most widely used frameworks to explain the relationship between learning and the use of games have been the theory of gamified learning and the self-determination theory (SDT) [30,[41][42][43]. Very succinctly (see a longer description [30,34,[41][42][43][44]) the theory of gamified learning [34] postulated that GBL influences learning through four components-such as instructional content, behaviors and attitudes, game characteristics, and learning outcomes-being the critical issue to the success of any GBL effect that "the instructional content in place is already effective" [34] (p. 9). Self-determination theory (SDT) postulated that "an understanding of human motivation requires a consideration of innate psychological needs for competence, autonomy, and relatedness" [43] (p. 227).…”
Section: Does Game-based Learning Work In Hies? Its Theoretical Foundationmentioning
confidence: 99%
“…In fact, the quality of instructional content is essential: if this content does not help college students to learn, gamified learning itself cannot produce learning [50]. Second, the game characteristics should help support psychological needs such as competence, autonomy, and empathy [43][44][45][46]50]. In this sense, the combination of collaboration (e.g., playing the game in teams) and competition (for example, the winning team is getting an award) could positively affect learning-related behaviors and outcomes [30].…”
Section: Does Game-based Learning Work In Hies? Its Theoretical Foundationmentioning
confidence: 99%
“…Gamification techniques or the art of employing games in the classroom [ 15 ] are a complement to increase the extrinsic motivation. Although games provide freedom in learning, where failure allows learning without fear, thus increasing student engagement [ 16 ], the use of games is being questioned [ 17 , 18 , 19 , 20 ]. In a review study, Hamari, Koivisto and Sarsa (2014) [ 18 ] concluded that gamification studies are limited by methodological problems such as small sample sizes, a lack of comparison groups (gamified and non-gamified experiences), short treatments, singular assessments or a lack of validated measures.…”
Section: Introductionmentioning
confidence: 99%
“…Respectively, application of gamification technologies for involvement of students into education seems to be attractive, though, it requires systematization of theoretical knowledge of main aspects of this concept as well as determination of already revealed advantages and disadvantages of gamification [4,5].…”
Section: Introductionmentioning
confidence: 99%